Characteristics of Caregivers Caring for Elderly People with Dementia - Syapri Pardiansah; Rika Sabri; Tasman Tasman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Elderly individuals often experience physical, social, and psychosocial decline, leading to various health issues, including dementia. In Padang City, the number of dementia cases increased significantly, reaching 458 in 2022. Caregivers play a crucial role in caring for elderly people with dementia, despite facing significant physical and psychological burdens. Objective: This study aims to describe the characteristics of caregivers caring for elderly people with dementia in Padang City in 2023. Method: This descriptive observational study involved 122 caregivers as respondents. Data were collected through direct interviews and analyzed using univariate tests to observe the frequency distribution of each variable studied. The study was conducted from June 2023 to April 2024. Results: The study results showed that the most common age group of respondents (52.5%) was young adults ≤ 40 years old. The majority of caregivers had a basic/secondary education level (97%), and 20.5% had higher education. Regarding marital status, 18.9% were unmarried, 27.9% were divorced, and 54.1% were married. Conclusions: The characteristics of caregivers in Padang City indicate that age, education, marital status, and gender are important variables influencing the quality of care for elderly people with dementia. This study highlights the need for specific support for caregivers to enhance their skills and knowledge, as well as interventions to alleviate the physical and psychological burdens they experience.